Sound the Trumpet: The United States and Human Rights Promotion - Haas, Lawrence J. (Rowman & Littlefield Publishers, 2012)
In Sound the Trumpet, Lawrence J. Haas examines the effort by America’s leaders and its people, its government and private institutions, to use the force of our ideals, the strength of our economy, the power of our military, and the influence of our culture to advance freedom and democracy around the world. Focused on the period since World War I1 – when human rights promotion became a central feature of U.S. foreign policy – Haas explores what Presidents and Congresses have done, the tools they have used, the results they have achieved, and the obstacles that have stood in their way. Writing in a concise, accessible style that will engage all readers interested in U.S. foreign policy, he tells a story of dramatic success that is somewhat offset by tragic errors and missed opportunities; of idealism and its practical limits; of clashes between America’s long-term goal of advancing freedom and democracy and such short-term goals as protecting national security, ensuring regional stability, and guaranteeing access to natural resources. Most strikingly, this story demonstrates America’s unique and enduring power to shape the course of history and make the world a safer, more prosperous place. Haas argues forcefully that, for all of our missed opportunities and tragic errors, the world is a better place because of our efforts.